A Brief History of De Novo Protein Design: Minimal, Rational, and Computational. Issue 20 (1st October 2021) - Woolfson, Derek N.
Graphical abstract: Highlights: De novo protein design is a maturing and expanding field of research. Approaches include minimal, rational and increasingly computational design. Over 100 high-resolution structures of de novo proteins have now been determined. Challenges remain to improve forcefields, incorporate dynamics, and add binding and catalysis. Marrying rational design and computational design should help address these challenges. Abstract: Protein design has come of age, but how will it mature? In the 1980s and the 1990s, the primary motivation for de novo protein design was to test our understanding of the informational aspect of the protein-folding problem; i.e., how does protein sequence determine protein structure and function? This necessitated minimal and rational design approaches whereby the placement of each residue in a design was reasoned using chemical principles and/or biochemical knowledge. At that time, though with some notable exceptions, the use of computers to aid design was not widespread. Over the past two decades, the tables have turned and computational protein design is firmly established. Here, I illustrate this progress through a timeline of de novo protein structures that have been solved to atomic resolution and deposited in the Protein Data Bank. From this, it is clear that the impact of rational and computational design has been considerable: More-complex and more-sophisticated designs are being targeted with many being resolved to atomic resolution. Furthermore, our ability to generate and manipulate synthetic proteins has advanced to a point where they are providing realistic alternatives to natural protein functions for applications both in vitro and in cells. Also, and increasingly, computational protein design is becoming accessible to non-specialists. This all begs the questions: Is there still a place for minimal and rational design approaches? And, what challenges lie ahead for the burgeoning field of de novo protein design as a whole?